Geothermal Exploration in Some Interest Geothermal Area in Republic of Yemen. (March 2019) - Al-Sabri, A; Al-Kohlani, T; Al-Nethary, M; Sharian, A; Al-Dukhain, A; Al-Hosam, A; Al-Hosam, M; Sultan, M.
Abstract: The first geothermal area (Al Lisi–Isbil Geothermal field) is located about (100) km from Sana'a capital city of Republic of Yemen, and the second geothermal area (Alsyani – Algandeah Geothermal field) is located about (250) km from Sana'a capital city of Republic of Yemen. In addition, the third geothermal area (Red Sea geothermal area) is located about (290) km from Sana'a capital city of Republic of Yemen. The geothermal mapping was carried out in (Al Lisi and Isbil and Alsyani – Algandeah Geothermal field) in the western area of Yemen. The rocks type in Al Lisi–Isbil Geothermal area was classified To six group, trap series, the post trappic volcanic activity, Isbil volcanic complex, Al Lisi volcanic complex, Basaltic Fissure volcanism and recent and active sedimentary deposits, The main structural feature are trend (NNE-SSW), (NE-SW), The rocks type in the second geothermal area Alsyani – Algandeah Geothermal area was classified to (4) type of Rocks, Tertiary Volcanic (Basalt, Rhyolite, and Tertiary intrusive rocks), Tawilah Sandstone Group, Medj-Zir Sandstone and Quaternary Deposits. The main structural feature is trend (NE-SW). In Al Lisi and Isbil Geothermal area The Geothermal manifestations (steam, clay alteration and slight alteration)common in many deferent site in the Geothermal area, two types of alteration zones are distinguished slight alteration mostly characterized by slight color change of the Brownish, reddish, yellowish to white colors and also involving some silica minerals (opal) and calcite veins and the some altered rocks assume a whitish color due to the presence of opline silica, clay minerals and iron oxides. In addition, the Albit, Montomornillonite, Biotite, Kaolinite, Chlorite Quartz, and Calcite are the individual minerals obtained by analysis (X-Ray) for samples taken from Al Lisi and Isbil Geothermal area. The temperatures of steam that exceed 92°C and They are 118 hot well in the area the temperature between (25°C) to (59°C). And the Geothermal manifestations(slight alteration)In Alsyani–Algandeah Geothermal area are common in many deferent site in the Geothermal field, one types of alteration zones are distinguished slight alteration mostly characterized by slight color change of the Brownish, reddish, to yellowish colors and also involving some silica minerals (opal) and calcite veins and the some altered rocks assume a Brownish, reddish and yellowish color due to the presence of opline silica, calcite veins, clay minerals and iron oxides. In addition, the limonite, Heulandite, Quartz, and Calcite are the individual minerals obtained by analysis (X-Ray) for samples taken from Alsyani–Algandeah Geothermal area. They are (42) hot well in the area the temperature between (27°C) to (75°C), the thermal wells to 340 meters deep (75°C), are in the area. Also The Red Sea geothermal area is located in west area of western Yemen volcanic part, was covered by drilling is does not exceed 3000 km 2, but data from several areas throughout the world, including neighboring countries such as Ethiopia yielded similar temperatures and geothermal gradients. In the Present, the temperature logs from the boreholes show temperatures of 190°C at 2458 m depth in the Red Sea geothermal area.